Eucommia ulmoides Oliv. leaf extract: Effects on growth, antioxidant capacity, and lipid metabolism in Red swamp crayfish (Procambarus clarkii) - Dan Yang; Wenbo Sun; Mengdan Hou; Chuanbo Xiao; Honghao Jin; Yong Lin; Dapeng Wang; Hua Ye; Hui Luo (Aquaculture Reports)
The addition of Eucommia ulmoides Oliv. leaf extract (ELE) enhances growth, immunity and antioxidant capacity in crustaceans, which has not been studied on the red swamp crayfish (Procambarus clarkii). Hence, this study aimed to investigate the effect of ELE on the growth, antioxidant capacity, digestive enzymes activities, and lipid metabolism of red swamp crayfish. A total of 240 individuals of red swamp crayfish were randomly assigned to four groups. Each group was fed with feed a diet supplemented with varying doses of ELE: 0 g/kg (CK), 0.5 g/kg (T2), 1.0 g/kg (T3), and 1.5 g/kg (T4). After 30 days, the results indicated that T2 group exhibited a significantly higher final average weight, weight gain rate, and specific growth rate compared to the CK (P<0.05). Significantly lower feed conversion ratios than the CK (P<0.05) were observed in the T2 and T3 groups. For antioxidant indicators, hepatopancreas superoxide dismutase (SOD) activity was observed to significantly increased in the T3 and T4 groups, while levels of malondialdehyde (MDA) in which were significantly reduced in hepatopancreas and hemolymph (P<0.05). Regarding biochemical indicators and intestinal function, significant enhancement of lipase (LPS) activity was observed in the T2 group, which decreased in the T4, compared to the CK (P<0.05). Moreover, significant decrease of the glucose (GLU), total triglyceride (TG), and total cholesterol (TC) content of the hemolymph (P<0.05) were observed in the T4 group. Transcriptome analysis revealed that differentially expressed genes in the T4 group were primarily enriched in peroxisome proliferator-activated receptor (PPAR), and lipid metabolism pathways. Furthermore, it seems that ELE supplements significantly upregulated the expression of apoa-II, acaox1, acox3, me1, and plin1 in the PPAR signaling pathway to regulate lipid metabolism. In conclusion, 0.5 g/kg and 1.5 g/kg ELL addition amount can enhance growth performance, antioxidant capacity, and lipid metabolism of red swamp crayfish.